Characteristics and factors influencing fast-food intake of young adult consumers from different socio-economic areas in Gauteng, South Africa - Van Zyl, Maryke Karin (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MNutr (Human Nutrition))--University of Stellenbosch, 2009.